INSTAGRAM SEBAGAI MEDIA GOVERNMENT PUBLIC RELATIONS KEMENTERIAN KOMUNIKASI DAN INFORMATIKA DI MASA PANDEMI COVID 19 - Andrea Amorita Tulung; sri ulya suskarwati; Virgin Cansa Abinta (Commed : Jurnal Komunikasi dan Media, 2021)
Since the spread of Covid-19 and declared a pandemic in Indonesia, the Government has provided various communication media as channels of information for the public. Instagram @kemenkominfo is an official account managed by the Ministry of Communications and Informatics (Kemenkominfo), which is one of the information centers about Covid-19 in Indonesia and is a new medium for it's Government Public Relations (GPR) during the Pandemic. This study aims to understand the concept of GPR Kemenkominfo through Instagram, by referring to the theory of Computer Mediated Communication (CMC) to understand the virtual communication process between government and public. A qualitative descriptive approach with a case study method is used by researcher to achieve research objectives. The results of the study is understanding of the range, speed, and amount of information on @kemenkominfo to provide knowledge and information according to public needs. Through Instagram, it provides understanding and direction regarding Covid-19 to public, as well as providing information dissemination services through an official account managed by Public Relations of the Ministry of Communications and Informatics. As a communicator and mediator in the spread of Covid-19 in Indonesia is the application of GPR concept during a pandemic. The Ministry of Communications and Informatics builds a conducive communication with the Indonesian people through the official Instagram account @kemenkominfo. Keyword:Government Public Relations, Instagram, Kemenkominfo, Computer Mediated Communication